Effects of application of soil amendments on runoff, soil loss and crop productivity in a fragile ecosystem of western India - RASHMI, I.; MINA, B.L.; KUMAR, KULDEEP; KUMAR, ASHOK; KUMAWAT, ANITA; KALA, S. (Journal of Soil and Water Conservation, 2024)
Runoff and soil loss are a serious threat to crop production in tablelands of Chambal ravines. Using soil amendments is an effective management tool in promoting soil health thereby preventing soil erosion and restoring crop productivity in arable lands of fragile ecosystem. A field experiment was conducted for three years (2017- 2019) to evaluate the effect of amendments (gypsum, crop residues (CR), farm yard manure (FYM) with recommended dose of nitrogen-phosphorus-potassium (RNPK) fertilizer dose) on soybean crop in Chambal ravine region. Highest runoff coefficient and soil loss was recorded in control (29.1% and 4.60 Mg ha-1) plots and lowest in RNPK + Gypsum + CR (15.4% and 1.73 Mg ha-1). Combined application of gypsum and organic amendments reduced runoff and soil loss by 40-43% and 58-60%, respectively over control. Runoff and soil loss reduction was reflected in improved soybean yield under the combined amendment treatments. Soil amendments (gypsum, FYM, CR, with fertilizers) thus could be a better choice for resource conservation, sustaining crop yield and restoring degraded land thereby reversing land degradation process in ravine ecosystem of western India.